Promoting recovery capital among college students in recovery on a campus developing a collegiate recovery program - Michael J. Broman; Michael J. Broman; Jhuma Acharya; Elizabeth A. Bowen; Emily Pasman; Erin Marks; Erin Marks; Jeffrey G. Kuentzel; Stella M. Resko; Stella M. Resko (Frontiers in Adolescent Medicine, 2025)
IntroductionRecovery capital is important to substance use recovery among general populations and among college students in recovery. Demographic factors and various psychosocial variables have been associated with recovery capital in studies including adults in the general population. However, recovery capital has received limited research attention in the context of collegiate recovery, and there has been little empirical evaluation of factors that might be linked with recovery capital among college students. As more collegiate recovery programs are developed to support students in recovery, these programs should implement features to augment students’ recovery capital.MethodsWe conducted a needs assessment on a campus with a newly developing collegiate recovery program. Students in recovery (n = 86) were asked to complete the 28-item Multidimensional Inventory of Recovery Capital (MIRC). They were also asked about sociodemographic and recovery-related factors including length of time in recovery, recovery pathway, perceived discrimination, mental health challenges, quality of relationships, and financial well-being. A multiple regression analysis was conducted to assess relationships between these variables and recovery capital.ResultsStudents reported a moderate level of recovery capital (M = 82.55, SD = 13.64). Students who reported fewer mental health challenges in the past 30 days (β = −.25, t = −2.79, p = .006), better quality of relationships in the past week (β = .27, t = 3.41, p = .001), and greater financial well-being (β = .38, t = 4.69, p < .001) had greater recovery capital. Sociodemographic variables, recovery length, recovery pathway, and perceived discrimination were not associated with recovery capital.DiscussionTo our knowledge, this is the first study to identify associations between recovery capital as measured by the MIRC and various sociodemographic and recovery-related factors among a sample of college students in recovery. As such, this study extends previous work with updated knowledge of how students can be supported in their efforts to increase recovery capital. Future research can build on this study by utilizing the MIRC on various types of campuses and by assessing recovery capital among college students longitudinally.